Perbandingan Pengaruh Latihan Wessel Pass & Loop Skip Terhadapi PeningkataniOtot Tungkai PadaiSiswa Kelas X SMK PGRI Cikoneng - Tedy Rizky Nurhakim; Gani Kardani; Ucu Abdul Ropi; Mohamad Rezha (Universitas Galuh, 2024)
ABSTRACTPhysical Education and Health (Penjaskes) plays a crucial role in fostering a healthy lifestyle and improving student fitness. The Independent Curriculum (Kurikulum Merdeka) encourages students to be active, independent, and capable of developing physical fitness, including leg muscle power, which is essential for sports activities such as kicking, jumping, and running. However, many tenth-grade students at SMK PGRI Cikoneng still have low leg muscle power. Power is a crucial component in supporting performance in various sports. Plyometric training has been proven effective in increasing power, especially through explosive movements. Two forms of plyometric training that are suitable and engaging for students are the wessel pass and the loop skip. Both exercises are game-like and adhere to plyometric principles, although they have limitations in loading. Based on this, this study was conducted to determine and compare the effects of wessel pass and loop skip training on increasing leg muscle power at tenth-grade students at SMK PGRI Cikoneng. Keywords: (Leg muscle power, Plyometric training, Wessel pass, Loop skip, Vocational school students) ABSTRAKPendidikan Jasmani dan Kesehatan (Penjaskes) berperan penting dalam membentuk gaya hidup sehat dan meningkatkan kebugaran siswa. Dalam Kurikulum Merdeka, siswa didorong untuk aktif, mandiri, dan mampu mengembangkan kebugaran jasmani, termasuk power otot tungkai yang sangat dibutuhkan dalam aktivitas olahraga seperti menendang, melompat, dan berlari. Namun, banyak siswa kelas X SMK PGRI Cikoneng masih memiliki power otot tungkai yang rendah. Padahal, power merupakan komponen penting dalam menunjang performa di berbagai cabang olahraga. Latihan pliometrik terbukti efektif untuk meningkatkan power, terutama melalui gerakan eksplosif. Dua bentuk latihan pliometrik yang sesuai dan menarik bagi siswa adalah wessel pass dan loop skip. Kedua latihan ini berbentuk permainan dan sesuai dengan prinsip pliometrik, meskipun memiliki keterbatasan pembebanan. Berdasarkan hal tersebut, penelitian ini dilakukan untuk mengetahui dan membandingkan pengaruh latihan wessel pass dan loop skip terhadap peningkatan power otot tungkai siswa kelas X SMK PGRI Cikoneng. Kata Kunci:(Power otot tungkai, Latihan pliometrik, Wessel pass, Loop skip, Siswa SMK)